Nutritional Assessment and Maternal Perception of Toddler Body Size using Toddler Silhouette Scale in Nigeria a Developing Country - Oluwafunmilayo Funke Adeniyi, MBBS, FMC (Paed), MSC (International Journal of Maternal and Child Health and AIDS, 2018)
Background and Objectives: The toddler silhouettes scales have been validated in the caucascian population in developing countries but in the African population, the use of these scales is yet to be evaluated. The aim of this study was to determine the perception of mothers on the body size of toddlers using a validated scale in an African population.